2009
DOI: 10.1007/s00431-009-1011-3
|View full text |Cite
|
Sign up to set email alerts
|

A heritable cause of cleft lip and palate—Van der Woude syndrome caused by a novel IRF6 mutation. Review of the literature and of the differential diagnosis

Abstract: This report emphasizes the role of the clinician in recognizing the clinical variability and the genetic heterogeneity of CL/P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
6
0
2
Order By: Relevance
“…Mutations in any of the coding or non‐coding exons of IRF6 result in VWS, whereas mutations predominantly affecting one residue encoded by exon 4 and a few other mutations in exons 3, 4, 6 and 9 have been reported to cause PPS (4, 6, 12–28). These mutations have been reported in patients of diverse nationalities but there are no reports of IRF6 mutations from South Asia.…”
mentioning
confidence: 99%
“…Mutations in any of the coding or non‐coding exons of IRF6 result in VWS, whereas mutations predominantly affecting one residue encoded by exon 4 and a few other mutations in exons 3, 4, 6 and 9 have been reported to cause PPS (4, 6, 12–28). These mutations have been reported in patients of diverse nationalities but there are no reports of IRF6 mutations from South Asia.…”
mentioning
confidence: 99%
“…This was followed by parametric linkage analysis, the trait model (mode of inheritance, disease-allele frequency, and penetrance of genotypes). 34 Since the parameters of the disease model were uncertain, in the initial genome scan, the evidence of linkage with a nonparametric, penetrance-independent, affected-only, and allele-sharing model was assessed. On finding significant evidence of linkage by exceeding the predetermined threshold (P.005) with an allele-sharing method, a range of parametric models to the data were fitted.…”
Section: Discussionmentioning
confidence: 99%
“…So far, globally available reports show that VWS is caused by mutations in the IRF6 gene located on chromosome 1q32·2 (Kondo et al, 2002;Ferrero et al, 2010;Leslie & Marazita, 2013). Recently, Indian studies on VWS reported that the critical region on Fig.…”
Section: Discussionmentioning
confidence: 99%